1988
DOI: 10.1093/infdis/157.6.1193
|View full text |Cite
|
Sign up to set email alerts
|

Increased Macrophage Division in the Synovial Fluid of Goats Infected with Caprine Arthritis-Encephalitis Virus

Abstract: Macrophages are a major component of the arthritic lesions induced by the lentivirus caprine arthritis-encephalitis virus (CAEV). Using autoradiography and the appearance of mitotic figures to detect dividing macrophages, we found that 2.1% +/- 0.2% of synovial fluid macrophages from uninfected goats are dividing and that after infection with CAEV the percentage increases three- to sixfold. The enhanced macrophage division was not associated with increased dividing of blood monoblasts. The amount of macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…(c) Transit time of immature circulating macrophages to the tissues may be increased. Lentivirus infection of monocytes and macrophages results in activation of the cells, as indicated by increased phagocytosis, adherence, motility, production of superoxide anion, esterase staining [3] and migration inhibition [2] in vitro, increased macrophage division in vivo [16], increased interferon production by lymphocytes cocultured with infected macrophages [31] and increased expression of Class II major histocompatibility antigens [45]. Alteration in the rate of maturation and migration to tissue may be affected as well.…”
Section: Discussionmentioning
confidence: 99%
“…(c) Transit time of immature circulating macrophages to the tissues may be increased. Lentivirus infection of monocytes and macrophages results in activation of the cells, as indicated by increased phagocytosis, adherence, motility, production of superoxide anion, esterase staining [3] and migration inhibition [2] in vitro, increased macrophage division in vivo [16], increased interferon production by lymphocytes cocultured with infected macrophages [31] and increased expression of Class II major histocompatibility antigens [45]. Alteration in the rate of maturation and migration to tissue may be affected as well.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst resident macrophages in normal tissue are relatively stable and long-lived cells, there is in fact a slow, constant rate of turnover as senescent cells are replaced by monocytes from the blood or by local proliferation (Oehmichen & Gruninger, 1974;Oehmichen, 1978;Ling, 1979a; Blusse van oud Alblas & van Furth, 1979;van Furth et al, 1980;Jutila & Banks, 1988). The turnover rates of macrophage populations in various tissues are low.…”
Section: Origin and Normal Turnovermentioning
confidence: 99%
“…However, we and others have shown that a small percentage of human monocytes can enter the cell cycle in vitro in response to agents such as M-CSF and granulocyte M-CSF (GM-CSF) [20 -22]. We have termed this pre-sumably immature subpopulation proliferative monocytes (PM) [21][22][23][24] and have proposed they could enter sites of inflammation and contribute to the local macrophage proliferation, which has been observed clinically and in animal models of inflammation [25][26][27][28]. Surface marker analysis has been carried out following in vitro culture of PM [23], but their characteristics upon isolation and relationship to other subpopulations have not been examined.…”
Section: Introductionmentioning
confidence: 99%